Unveiling the kinetic versatility of aryl-alcohol oxidases with different electron acceptors - Serrano, Ana; Cinca-Fernando, Paula; Carro, Juan; Velázquez-Campoy, Adrián; Martínez-Júlvez, Marta; Martínez, Ángel T.; Ferreira, Patricia (Frontiers in Bioengineering and Biotechnology, 2024)
Aryl-alcohol oxidase (AAO) shows a pronounced duality as oxidase and dehydrogenase similar to that described for other Glucose-methanol-choline (GMC) oxidase/dehydrogenase superfamily proteins involved in lignocellulose decomposition.In this work, we detail the overall mechanism of AAOs from Pleurotus eryngii and Bjerkandera adusta for catalyzing the oxidation of natural aryl-alcohol substrates using either oxygen or quinones as electron acceptors and describe the crystallographic structure of AAO from B. adusta in complex with a substrate analogue. Kinetic studies with 4-Methoxybenzyl and 3-chloro-4-methoxybenzyl alcohols, including both transientstate and steady-state analyses, along with interaction studies, provide insight into the oxidase and dehydrogenase mechanisms of these enzymes. Although both enzymes show similar mechanistic properties, notable differences are highlighted in this study. In B. adusta, the AAO oxidase activity is limited by the reoxidation of the flavin, while in P. eryngii the slower step takes place during the reductive half-reaction, which determine the overall reaction rate. By contrast, dehydrogenase activity in both enzymes, irrespectively of the alcohol participating in the reaction, is limited by the hydroquinone release from the active site. Despite these differences, both AAOs are more efficient as dehydrogenases, supporting the physiological role of this activity in lignocellulosic decay. This dual activity would allow these enzymes to adapt to different environments based on the available electron acceptors. Moreover, the resolution of the crystal structure of AAO from B. adusta allowed us to compare their overall folding and the structure of the active sites of both AAOs in relation to their activities.